Pelvic Rocking Exercise as an Alternative Exercise Therapy to Reduce Back Pain in Pregnant Women - Imaniar Faulina; Sri Wahyuni; Heri Susanto; Nopi Nurkhasanah (Indonesian Journal of Global Health Research, 2025)
Back pain in pregnant women, particularly in the second and third trimesters, is often due to hormonal changes, the centre of gravity and increased body weight. Pelvic rocking is a safe and effective non-pharmacological therapeutic alternative to reduce this pain, with benefits such as reducing muscle tension, improving posture and increasing circulation. Objective: The aim of this study was to identify and summarise the scientific evidence on the effect of pelvic rocking on reducing back pain during pregnancy. Method: This research uses the systematic literature review (SLR) method published between 2020-2025, which is a structured approach to identifying, appraising and synthesising research relevant to a particular question. This research uses several available database sources in e-resources : Pubmed, ScinceDirect and Google Scholar. Results: The results showed that pelvic rocking is an effective alternative therapeutic exercise to reduce back pain in pregnant women. Conclusions: The conclusion of this study is pelvic rocking exercise techniques provides the same results in reducing back pain in pregnant women.